Vascularization of the hypotenar’s skin as the basis for raising the fasciocutaneous flap - Dražan Erić; Milan Milisavljević; Milomir Ninković; Siniša Kojić (Биомедицинска истраживања, 2010)
Introduction: The hypothenar’s skin is nourished by perforant cutaneous branches which pass across muscle, fascia and palmar aponeurosis. The aim of this work was determination of anatomic characteristics of vascular cutaneous territory of hypotenars as the basis for raising the flaps for the purpose of reconstruction of the defects on the hand. Methods: Micro morphological and morphometric researches have been done on 30 hands of cadavers of both sexes without pathological changes on the blood vessels of the hand. We selectively injected 10% dissolved douche gelatin in two colors into blood vessels of 10 hands . By injecting metyl-metacrylate into the arterial system of 20 hands and by corrosion in 40% solution KOH, we got plastic castings of the arterial network that we have used as the basis for all measures and space analyses in our research. Results: The trunk of the ulnar artery gives 3-6 cutaneous branches, average 4.1+/- 1.07, and their diameter was about 0.40 to 0.85 mm. Ulnar palmar digital artery of the little finger gives 5 to 9 cutaneous branches, average 7.6. Their diameter was from 0.35 to 0.70 mm. Superficial branch of deep palmar branch of the ulnar artery gives sprigs that vascularize the hypotenar’s skin, and they reach the skin through abductor digiti minimi muscle and flexor digiti minimi brevis muscle. That one gives from 2 to5 perforators for the skin of approximately half of the hypotenars, on average 3.70. Their diameter was from 0.25 to 0.70 mm. Cutaneous branches of the superficial palmar arch were reaching either through palmar aponeurosis or by its ulnar border in order to vascularize the radial border of the hypotenar eminence. Conclusion: Hypotenar’s skin is nourished by perforant cutaneous of ulnar artery trunk branches, ulnar palmar digital artery of the little finger, deep palmar branch of the ulnar artery and superficial palmar arch. Cutaneous branches of these arteries establish anasthomosises at all levels.
Keywords: hypotenar; vascularization; fasciocutaneous flaps